A brief insight into the use of plant products as green inhibitors for corrosion mitigation of aluminium and aluminium alloys. (2nd October 2022) - Namitha, K; Rao, Padmalatha; Rao, Suma A.
ABSTRACT: Corrosion of metals is a universal phenomenon, and the economy of any nation is very much influenced by the loss due to corrosion which is about 4–5% GDP or equivalent to the budget earmarked for education. Aluminium and its alloys are normally corrosion-resistant because the surface gets converted into a thin oxide layer over a period of time. But the metal and its alloys, in spite of oxidation, become highly vulnerable in chloride ion environment and significant variation in pH of the medium. However, corrosion can be controlled by using certain organic heterocyclic compounds as inhibitors. Among them, the use of green inhibitors, mainly in the form of phytochemical plant products, are, of late, tried to avoid the toxicity of medium stored in aluminium and its alloy vessels. This review paper consolidates literature on the extent and type of corrosion taking place and the use of different plant extracts as inhibitors. A few of them have inhibition efficiency in the range of 90–99%, even in stringent corrosive conditions. Through this brief overview, we have updated the available literature of plant products that are successfully utilised as inhibitors to mitigate corrosion of aluminium alloys under varying experimental conditions.